2017
DOI: 10.4028/www.scientific.net/nhc.13.162
|View full text |Cite
|
Sign up to set email alerts
|

Features of Light Conversion Process with Covering Materials Containing Quantum Dots and their Application in Agriculture

Abstract: Improving the efficiency of greenhouses is one of the most promising directions in development of agriculture. New perspectives in this field opened up with the development of the new methods of synthesis of a new generation of photoluminescent materials based on colloidal semiconductor photoluminophores (so-called "quantum dots"). It is shown that use of the covering materials containing quantum dots can significantly increase yields. Moreover, introduction of these quantum dots into commercial production can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Further investigation revealed that carbon QDs can enhance the photosystem activity by improving the electron transfer rate and also affect other critical indicators in photosynthesis, such as chlorophyll content and motivates RuBisCO activity [54]. QDs convert a given fraction of the solar spectrum into one that can be more effectively utilized by photosynthetic light reactions so; QDs provide an efficient and cost-effective light source alternative with proper spectral composition to intensify the photosynthetic rate of plants [55,56]. According to a study by Moaveni et al [57], TiO 2 NPs can increase pigment content and facilitate the transportation of photosynthetic materials by recovering chlorophyll structure and light sorption.…”
Section: Effect Of Tio 2 Qds On Chlorophyll Contents Of Hibiscus Plantsmentioning
confidence: 99%
“…Further investigation revealed that carbon QDs can enhance the photosystem activity by improving the electron transfer rate and also affect other critical indicators in photosynthesis, such as chlorophyll content and motivates RuBisCO activity [54]. QDs convert a given fraction of the solar spectrum into one that can be more effectively utilized by photosynthetic light reactions so; QDs provide an efficient and cost-effective light source alternative with proper spectral composition to intensify the photosynthetic rate of plants [55,56]. According to a study by Moaveni et al [57], TiO 2 NPs can increase pigment content and facilitate the transportation of photosynthetic materials by recovering chlorophyll structure and light sorption.…”
Section: Effect Of Tio 2 Qds On Chlorophyll Contents Of Hibiscus Plantsmentioning
confidence: 99%
“…Extraction of chloroplasts: refer to the method of Pan et al [8,24]. To extract chloroplasts, sucrose buffer (0.4 M (mol/L) sucrose, 0.01 M KCl, 0.03 M Na 2 HPO 4 , 0.02 M KH 2 PO 4 ) was prepared with a pH of 7.3, then refrigerated at 4 • C. The mortar and sucrose buffer were also pre-cooled in the refrigerator after preparation.…”
Section: Effect Of Cqds and N-cqds On Photosynthetic Activitymentioning
confidence: 99%
“…However, plants only convert 2-4% of light into energy, and current research is focused on improving photosynthesis efficiency during plant growth. Researchers have proposed various strategies to address the key issue, including genetic improvement of the plant itself [7,8] and the artificial regulation of the plant growth cycle with supplemental light or light-converting materials [9]. Compared to the time-consuming and challenging process of genetic engineering modification [10], artificial regulation proves to be more efficient and economically beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Various materials, including inorganic nanomaterials like quantum dots [7,8], along with organic dyes [9,10], hold promise for enhancing greenhouse plant photosynthesis. Additionally, smart materials that can adjust optical properties and genetic engineering advancements, such as Sr 2 Si 5 N 8 :Eu 2+ particles, offer opportunities to optimize light absorption and distribution [11][12][13], ultimately improving crop productivity and addressing global food security challenges.…”
Section: Introductionmentioning
confidence: 99%